(untitled) (LEARNing Landscapes, 2022)
Framing through the concept of precarity, we share our arts-based research on the experiences of creating a collaborative performance-making project focused on connecting students from different education levels, to create a film-dance integrated performance to advocate for social justice issues in education. We, as instructors and researchers, embarked on an arts-based research journey creating sketches, poems, videos, and a dance performance to analyze and represent our research findings. Our performance from the performative inquiry shows our understanding of the collaboration project through the same art form we required our students to utilize: film and dance-integrated arts performance.